Pengaruh Lokasi, Pemasaran, dan Pelayanan terhadap Kepuasan Wisatawan Lokal Curug Lawe Benowo Kalisidi - Pradipta, Amrizal Eka; Amron, Amron; Wardhani, Masitha Fahmi; Purusa, Nanda Adhi (Jurnal EMT KITA, 2026)
This study aims to analyze the influence of location, marketing, and service on the satisfaction of tourists at Curug Lawe Benowo Kalisidi. The data used in this study comes from the distribution of questionnaires via Google Form and obtained with a total of 118 respondents. The sampling method in this study uses a purposive sampling method with the criteria that visitors have visited at least 2 times in the last 6 months. The analysis tool for processing data uses the SPSS 25.0 testing application. The method for analyzing this study is based on quantitative primary data, the use of multiple linear research methods, then the testing stages carried out are: validity test, reliability, classical assumption test, multiple linear regression, t test, F test and coefficient of determination. The results of the study show that: (1) Location contributes positively and significantly to the satisfaction of tourists at Curug Lawe Benowo Kalisidi. (2) Marketing has a positive and significant contribution to the satisfaction of tourists at Curug Lawe Benowo Kalisidi. (3) Service contributes positively and significantly to increasing the satisfaction of tourists at Curug Lawe Benowo Kalisidi.